MARKETING COMMUNICATION STRATEGY OF PAWNSHOP AGENTS IN SEEKING CUSTOMERS AND MARKETING SERVICES AT THE PAWNSHOP IN TEBING TINGGI CITY - Muhammad Tabrani; Abdul Karim Batubara (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to determine the marketing communication strategies used by Pegadaian agents in finding customers and marketing services in Tebing Tinggi City. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, observations, and documentation of Pegadaian agents operating in the Tebing Tinggi City area. The results show that Pegadaian agents' marketing communication strategies focus on interpersonal communication that is persuasive, familial, and trust-based. The strategies used include face-to-face communication (personal selling), word of mouth communication (word of mouth), and communication through social media and WhatsApp. Face-to-face communication is the main strategy because it can build trust directly, while word of mouth communication is effective in disseminating information through the community's social environment. The use of social media and WhatsApp plays a supporting role in delivering information, providing services, and maintaining relationships with customers. However, Pegadaian agents still face several obstacles, such as negative public stigma towards Pegadaian, low financial literacy, limited number of agents, and competition with other financial institutions. Therefore, a more planned and sustainable communication strategy is needed so that Pegadaian service marketing can run more effectively.